Design of a low carbon economy model by carbon cycle optimization in supply chain - Ding, Jingwen (Frontiers in Ecology and Evolution, 2023)
Concerning economic globalization, enterprises must work with the cooperative partner to obtain more profits and overall planning of the supply chain has become a new focus for enterprise development. This paper studies the joint emission reduction of the supply chain in green low-carbon economy development and achieve joint emission and economic cost reduction through the optimization of carbon emission and economic dispatch. The paper firstly uses the multi-agent model to complete the full-cycle modeling of carbon emission and economic cost; Secondly, the simulated annealing-adaptive chaos-particle swarm optimization (SA-ACPSO) method is used to optimize various parameters in the model to achieve emission and cost reduction, and the results show that after the optimization, the economic cost is reduced by 0.07 and the carbon emission is also reduced by 0.16; Finally, the practical test of the model is conducted with the collected data from the local company. The results show that the multi-objective optimization model of a joint enterprise supply chain is significantly better than single optimization in terms of emission reduction, which provides new ideas for a green economy and technical support for the global planning of supply chain integration.